2018
DOI: 10.3389/fphys.2018.00830
|View full text |Cite
|
Sign up to set email alerts
|

Altitude Acclimatization Alleviates the Hypoxia-Induced Suppression of Exogenous Glucose Oxidation During Steady-State Aerobic Exercise

Abstract: This study investigated how high-altitude (HA, 4300 m) acclimatization affected exogenous glucose oxidation during aerobic exercise. Sea-level (SL) residents (n = 14 men) performed 80-min, metabolically matched exercise (trueV˙O2 ∼ 1.7 L/min) at SL and at HA < 5 h after arrival (acute HA, AHA) and following 22-d of HA acclimatization (chronic HA, CHA). During HA acclimatization, participants sustained a controlled negative energy balance (-40%) to simulate the “real world” conditions that lowlanders typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 43 publications
5
46
0
Order By: Relevance
“…Participants were randomized to groups and were provided equal volumes of flavor-matched carbohydrate (CHO; 65.25 g fructose + 79.75 g glucose ingested at 1.8 g/min, n = 8, 3 standard and 5 high protein) and placebo (PLA; n = 6, 4 standard and 2 high protein) beverages during 80 min of metabolically-matched, steady-state treadmill walking at SL (day 7), 5 h after arriving at HA (acute HA), and after 22 days of acclimatization and energy deficit (chronic HA, day 42). As previously reported [13] treadmill speed, grade, absolute oxygen uptake (L/ min), and metabolic rate were not different across study phases. All time trials were completed at the same time of day (between 1130 and 1230) and participants were fasted prior to the start of exercise.…”
Section: Exercise and 2-mile Time Trialsupporting
confidence: 80%
See 4 more Smart Citations
“…Participants were randomized to groups and were provided equal volumes of flavor-matched carbohydrate (CHO; 65.25 g fructose + 79.75 g glucose ingested at 1.8 g/min, n = 8, 3 standard and 5 high protein) and placebo (PLA; n = 6, 4 standard and 2 high protein) beverages during 80 min of metabolically-matched, steady-state treadmill walking at SL (day 7), 5 h after arriving at HA (acute HA), and after 22 days of acclimatization and energy deficit (chronic HA, day 42). As previously reported [13] treadmill speed, grade, absolute oxygen uptake (L/ min), and metabolic rate were not different across study phases. All time trials were completed at the same time of day (between 1130 and 1230) and participants were fasted prior to the start of exercise.…”
Section: Exercise and 2-mile Time Trialsupporting
confidence: 80%
“…We suspect the discrepancy between our data and those by Fulco et al [9] are due, in part, to the apparent inability to effectively oxidize exogenous carbohydrate upon initial exposure to HA. In the same study, we demonstrated a 52% reduction in exogenous carbohydrate oxidation and a corresponding increase in endogenous carbohydrate oxidation (i.e., blood glucose, muscle and liver glycogen) during the 80 min steady-state exercise bout with acute HA exposure compared to SL 13 . The mechanisms accounting for the reduction in exogenous carbohydrate oxidation during acute HA exposure are not known, but may be attributable to adjustments in glycemic regulation, as participants were markedly hyperinsulinemic, which inhibited lipolysis and likely accelerated glycogenic flux.…”
Section: Discussionmentioning
confidence: 52%
See 3 more Smart Citations